GLOBAL CITIZENSHIP OF INDONESIA AND PUBLIC CITIZENSHIP EDUCATION: RECONSTRUCTING MEMBERSHIP, IDENTITY, AND SOVEREIGNTY IN DIASPORA POLICY - Elin Wijaya (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This article examines Indonesia's Global Citizenship (GCI) as a new policy that offers permanent residence permits to foreign nationals with strong ties to Indonesia in response to the polemic surrounding dual citizenship and diaspora issues. Using document analysis and conceptual analysis, this study places GCI within the framework of citizenship philosophy: citizenship as legal status, political membership, and participatory practices. Conceptual findings show that GCI reconstructs membership through the recognition of blood ties, kinship, and history without changing the principle of single citizenship sovereignty. The article then interprets the GCI as a form of public citizenship education, namely the way the state shapes a collective understanding of who is included in “us,” how loyalty is interpreted, and how the contributions of the diaspora are legitimized in the policy space. The implications discussed include the limits of citizen and state obligations, the risk of exclusion based on kinship categories, and the need for public ethical principles so that diaspora policies are not merely economistic, but oriented towards justice and accountability.